Site‐Selective Functionalization of Sila‐Adamantane and Its Ensuing Optical Effects. Issue 31 (14th June 2022) - Siu, Timothy C.; Imex Aguirre Cardenas, M.; Seo, Jacob; Boctor, Kirllos; Shimono, Miku G.; Tran, Isabelle T.; Carta, Veronica; Su, Timothy A.
Abstract: The first syntheses of functionalized sila‐adamantanes via site‐selective reactions are described. Mechanistic inquiry into the isomerization of sila‐adamantane revealed new approaches for installing halides at the 2‐position of the cluster. Meanwhile, isomerization via Lewis acid catalysts with non‐nucleophilic counteranions provided access to sila‐adamantane on the gram‐scale, enabling us to discover strategies for substituting its 1‐, 3‐, 5‐, and 7‐positions with identical or distinct functional groups. Optical absorbance and density functional theory studies show that σ‐withdrawing substituents at the 1‐position strongly perturb optical absorbance in sila‐adamantane, whereas substituents at the exocyclic and 2‐position are optically inert. As silicon diamondoids are atomically precise models for silicon nanocrystals, our findings suggest that passivation at tertiary surface sites carries an outsized impact on the optical properties of surface‐functionalized Si nanocrystals. Abstract : Mechanistic insight into the isomerization synthesis of sila‐adamantane enables the regioselective functionalization of sila‐adamantane at its 1‐, 2‐, 3‐, 5‐, and 7‐positions. Substitution at the 1‐position of the cluster core significantly impacts optical absorbance relative to exocyclic or 2‐substitution.